KORELASI ASPEK REINFORCING TERHADAP KUALITAS HIDUP LANSIA - Reggi Prathama; Amos Lellu; Janner Pelanjani Simamora; Riance Mardiana Ujung (Ensiklopedia of Journal, 2025)
Based on a preliminary survey conducted by researchers, it was found that most elderly respondents lived with their family members. This condition shows that the family is still the main environment for the elderly in their daily lives, both as a place to live and as a source of emotional and social support. However, preliminary observations also show variations in the quality of life of the elderly. Some elderly people show a good quality of life, while others have a relatively low quality of life. The purpose of this study is to determine the correlation between aspects of reinforcing family support and the quality of life of elderly people. The research design used in this study is cross-sectional. The study was conducted in a hospital in North Luwu Regency. The study was conducted in February 2024. The population consisted of all elderly people undergoing treatment. The sample consisted of 70 people. The sampling technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between family support (p value: 0.029) and the quality of life of the elderly. It is recommended that the families of the elderly provide more support to the elderly to improve their quality of life. Keywords: Family Support, Quality of Life, Elderly